Prevalence and associations of sarcopenia, obesity and sarcopenic obesity in end-stage knee osteoarthritis patients - Junyi Liao; Jie Chen; Wei Xu; Jia Chen; Xi Liang; Qiang Cheng; Yongli Tang; Wei Huang (BMC, 2023)
Abstract Objective To identify the prevalence of obesity, sarcopenia, sarcopenic obesity in end-stage knee osteoarthritis (KOA) patients and analyze influences of obesity and sarcopenia in the progression of KOA. Methods A cross-sectional study was carried out among end-stage KOA patients who consecutively admitted to Orthopedic Department for TKA. We suppose that the level of decreased physical activities would be influenced by unilateral or bilateral KOA. Patient information, albumin, hemoglobin, pace, step frequency, number of comorbid conditions were collected. Bioelectrical impedance analyzer was used to analyze body composition. Obesity, sarcopenia, sarcopenic obesity rate were analyzed with accepted diagnosis criteria. Correlations between body mass index (BMI) or age and fat mass (FM), appendicular skeletal muscle mass (ASM) were analyzed. Results 138 patients (male 30, female 108) in southwest of China including 67 patients with unilateral KOA and 71 patients with bilateral KOA were analyzed. No statistic difference was found in mean albumin, prealbumin and hematocrystallin, body composition values and number of comorbid conditions. We found that BMI was positively correlated with FM (Male: R2 = 0.7177, p < 0.0001, Female: R2 = 0.8898, p < 0.0001), ASM (Male: R2 = 0.2640, p = 0.0037, Female: R2 = 0.2102, p < 0.0001), FM index (FMI) (Male: R2 = 0.6778, p < 0.0001, Female: R2 = 0.8801, p < 0.0001), and ASM index (ASMI) (Male: R2 = 0.3600, p = 0.0005, Female: R2 = 0.4208, p < 0.0001) in end-stage KOA patients. However, age was not obviously correlated with FM or FMI (Male: FM, R2 = 0.006911, p = 0.3924; FMI, R2 = 0.7554, p = 0.0009196; Female: FM, R2 = 0.001548, p = 0.8412; FMI, R2 = 0.002776, p = 0.7822). And slightly negatively correlated with ASM (Male: R2 = 0.05613, p = 0.0136, Female: R2 = 0.01327, p = 0.5433) and ASMI (Male: R2 = 0.02982, p = 0.3615; Female: R2 = 0.03696, p = 0.0462). The prevalence of obesity, sarcopenia and obesity sarcopenia differs according to different diagnosis criteria. No difference in the occurrence rate of obesity was found between bilateral KOA and unilateral KOA patients, and occurrence rates of sarcopenia and sarcopenic obesity were statistically higher in bilateral KOA than that in unilateral KOA patients. Conclusions Obesity, sarcopenia and sarcopenic obesity are highly prevalent in end-stage KOA patients, sarcopenic obesity are more prevalent in bilateral KOA patients than that in unilateral KOA patients.